Assessing the impact of anthropogenic disturbances on water quality in the Sungai Nyior, Kuantan - Wan Nur Hafeza Haslinda, Wan Hassan (2017)
Nowadays, the condition of water pollution in Malaysia is becoming more serious because of the water quality is declining due to the anthropogenic activity that was carried out. Sungai Nyior has been chosen for this study of water quality which located in Balok Baru, Kuantan, Pahang with length and wide are 11.3 km and 20 m respectively. The objectives of this study were to evaluate the characteristics of current water quality in the study area based on National Water Quality Standard (NWQS) and Water Quality Index (WQI), Malaysia, to identify the possible factors or sources that influences the water quality of the river system and to make an appropriate suggestion for effective management of the water resources. To achieve the objectives, three times of water samples were collected monthly from September to November 2016. Physical, chemical and biological parameters were analyzed using standard methods. The WQI was calculated based on the concentration of pH, total suspended solid (TSS), ammonia nitrogen (NH3-N), chemical oxygen demand (COD), biochemical oxygen demand (BOD) and dissolved oxygen (DO). Other parameters that were analyse in this study were turbidity, temperature, electrical conductivity (EC), total hardness, selected heavy metal which are cadmium (Cd), copper (Cu) and chromium (Cr), total coliform and E.coli,. Result from the study showed the values of WQI at each station were in the range 51.9-76.5 that in the Class III. The WQI score value at Station 1, 2 and 3 were 54.20, 56.19, and 54.21 respectively. The status of this river was in polluted condition. In NWQS, the Sungai Nyior is classified under Class IV. The main factor of anthropogenic activities that influences the degradation of water quality was sewerage and drainage in a residential area, construction activities, livestock, agricultural and forested that near the river. Finally, the monthly monitoring and planning is necessary to improve the quality of the river and make policy to control the water quality.